PENGARUH MODAL KERJA DAN PENJUALAN TERHADAP LABA PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Muhidin, Muhidin; Wahyu, Didin Rasyidin; Yuliah, Yuliah (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2024)
This research observes fluctuations in working capital in pharmaceutical companies listed on the Indonesia Stock Exchange (BEI) during the 2018-2023 period and this research also explores the relationship between sales and net profit, with a focus on how sales can affect pharmaceutical companies' net profit.  This research aims to determine the effect of Working Capital and Sales on Net Profit in Pharmaceutical Companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2023 period. This research uses associative causality research methods with quantitative data types. 9 (nine) companies were selected from a total of 14 pharmaceutical companies as samples using the purposive sampling method. Analysis uses multiple linear regression with the help of SPSS version 26.0. The results of the t test show that partially, Working Capital and Sales have a significant effect on Net Profit, with a sig value below 0.05 for each working capital ratio of 0.023 with a value of tcount > ttable (2.347 > 2.007) and sales of 0.004 with value tcount > ttable (3.059 > 2.007). The results of the f test also show that simultaneously, these two ratios have a significant effect on Net Profit, with a calculated F value of 77.494 > F table 3.18 and a significant value of 0.000 < 0.05. Thus, the conclusion of this research is that both partially and simultaneously, Working Capital and Sales on Net Profit have a significant effect on Net Profit in the Pharmaceutical Companies studied